Literature review and sample training programs for safe return to training after the state of emergency - Approaches to return to strength and conditioning session for high-performance athletes at the Japan High Performance Sport Center I - Ogata, H.; Suzuki, E.; Yamashista, D.; Oishi, M.; Tamura, N. (Journal of High Performance Sport, 2021)
The COVID-19 pandemic has forced most athletes to be inactive, and they were unable to follow there normal training regimen. In Japan, there was the state of emergency from April to May in 2020, and all training facilities at the Japan High performance Sport Center were closed. The training gym's strength and conditioning coaches had to prepare for the re-opening of the gym. In an effort to support the return to training of the athletes, we had to consider possible risk factors and potential changes in the physical attributes following the periods of inactivity. we have developed our training programs by making the most of the limited available evidence.